The effect of a proposed mental training program on the level of offensive table tennis skills performance among players of the Palestinian national junior team - rasmi djaber, ramzi (sports creativity, 2025)
The study aimed to identify the effect of a proposed mental training program on the level of offensive table tennis skills performance among the players of the Palestinian national youth team. The experimental method was used with two groups, one experimental and the other control, for a sample of (21) players who were divided into two equal groups. The proposed program was implemented for a period of (1) weeks with a number of (11) training units, the duration of each unit being (13) minutes. The results of the study showed that there is a positive effect of the proposed mental training program on the level of offensive table tennis skills performance among the players of the Palestinian national youth team, in favor of the players who were subjected to the program at the expense of the players who were trained in the traditional way.